Yo vivo / Max Aub ;[estudio introductorio de Manuel Tarancón Fandos] - Tarancón,Manuel (1954-2004); Aub, Max (1903-1972)
Contiene: foto Max Aub, aǫs 30 | ed. facs. de: México : Tezontle, 1953. --1° ed.